Phase change functional material with wide temperature range and preparation method thereof
By preparing composite phase change materials with multiple phase change temperature intervals, the problem that a single phase change temperature interval in the prior art cannot meet the full temperature domain temperature control requirements of lithium-ion batteries is solved, and heat absorption under different working conditions is achieved The temperature control and thermal runaway suppression effect improve the safety of the battery.
Patent Information
- Application Number
- CN202411616947.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The single phase change temperature range of existing phase change materials cannot meet the temperature control needs of lithium-ion batteries in the full temperature domain, especially at high temperatures, which cannot effectively suppress thermal runaway.
Using raw materials such as polyethylene glycol, sodium acetate trihydrate, expanded graphite and epoxy resin glue, through high-temperature physical melting and high-speed stirring, composite phase change materials with two or more phase change temperature intervals are prepared to enhance their Thermal conductivity and high temperature resistance.
It realizes the heat absorption and temperature control requirements of lithium-ion batteries under different working conditions, effectively suppressing or delaying the occurrence of thermal runaway, and improving the safety and reliability of the battery.
Smart Images

Figure CN119463451A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of phase change composite materials, and in particular to a phase change functional material with a wide temperature range and a preparation method thereof. Background Art
[0002] Phase change materials refer to materials that undergo a physical transformation in a certain temperature range, thereby absorbing a large amount of heat, while maintaining the physical and chemical properties of the material unchanged. Therefore, phase change materials are regarded as a novel way of thermal design of lithium-ion battery heat pipe systems, which utilizes phase changes in a specific temperature range to absorb a large amount of heat, so that the temperature of lithium-ion batteries can be controlled in a more appropriate temperature range, thereby improving the safety of battery use and cycle life.
[0003] At present, many invention technologies have been disclosed for the preparation of composite phase change materials and in the field of thermal design of lithium-ion batteries. Public document CN2022109685719 discloses a phase change material with high thermal conductivity and high strength for use in a battery thermal management device. The phase change temperature of the disclosed phase change material is 45-50°C, a typical single phase change temperature zone. The introduction of foam metal and expanded graphite effectively solves the problems of low thermal conductivity and easy leakage of phase change materials. Public document CN2022107121815 discloses a composite phase change material technology of carbon-based aerogel loaded with modified polyethylene glycol. The prepared composite phase change material has a thermal conductivity of up to 0.6W / mK and a latent heat of up to about 160J / g, and there is only one phase change temperature domain. It can be seen from the above public documents that the current phase change material thermal management technology solution mainly focuses on low or medium temperature (<50°C) battery heat dissipation and temperature control, but studies have confirmed that the temperature triggered by lithium-ion batteries during thermal runaway is as high as 110°C or above. A single phase change temperature range cannot meet the temperature control requirements of the battery in the entire temperature range. It is urgent to develop a phase change temperature range that can cover the temperature control and heat dissipation requirements under normal operating conditions. At the same time, it is also necessary to take into account the suppression of the triggering of battery thermal runaway and reduce the continued deterioration of the battery into a serious thermal runaway safety accident. Summary of the invention
[0004] In response to the problem of the single phase change temperature range extracted above, the patent of the present invention discloses a material with wide-range phase change heat absorption and heat insulation functions and its preparation method. The disclosed case technology has typical two or more phase change temperature ranges. At the same time, the thermal conductivity of the composite material is improved by adding thermally conductive fillers, thereby realizing the heat absorption and temperature control requirements of the battery under different working conditions, satisfying the suppression of the triggering of thermal runaway or delaying the occurrence of thermal runaway of the battery, and improving the safety and reliability of the battery during use.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A phase change functional material with a wide temperature range and a preparation method thereof, characterized in that the wide-range phase change temperature endothermic insulation functional material comprises the following raw materials in weight: 15-30 parts of polyethylene glycol, 20-40 parts of sodium acetate trihydrate, 1-4 parts of expanded graphite, and 5-10 parts of epoxy resin glue; the polyethylene glycol weighed by weight is added to a stainless steel container, and the stainless steel container is placed in an oil bath pot with an oil temperature set to 100°C or above for heating and insulation, and the mixture of the sodium acetate trihydrate and the expanded graphite weighed by weight is further added to the liquefied polyethylene glycol solution, and stirred and fully dispersed by a stirrer at high speed, and the epoxy resin is further weighed by weight and added to the stainless steel container, and stirring is continued to make the mixture in the container fully and evenly mixed, and finally cooled to room temperature to prepare the wide-temperature phase change endothermic insulation functional material.
[0007] Furthermore, a phase change functional material with a wide temperature range and a preparation method thereof are provided, characterized in that the polyethylene glycol is 15-30 parts, preferably one or more of polyethylene glycol 2000 or polyethylene glycol 3000 or polyethylene glycol 4000 or polyethylene glycol 6000 or polyethylene glycol 8000 or polyethylene glycol 10000 or polyethylene glycol 20000 are mixed in proportion, and polyethylene glycols of different molecular weights have different phase change temperature ranges.
[0008] Furthermore, a method for preparing a wide-range phase change temperature heat absorption and heat insulation functional material is characterized in that the preparation of the second or more phase change temperature range composite materials adopts the following pretreatment steps:
[0009] (1) 20-40 parts of sodium acetate trihydrate;
[0010] (2) Weighing a certain amount of sodium acetate trihydrate and placing it in a glass beaker;
[0011] (3) adding 1-4 parts of the expanded graphite into a glass beaker, and weighing 1 part, 2 parts, 3 parts or 4 parts by weight;
[0012] (4) The expanded graphite is prepared by a high-temperature physical thermal expansion method. A certain mass of expandable graphite sheets is weighed and placed in a muffle furnace chamber. The temperature of the muffle furnace is raised to 900° C. for 60 minutes. After the temperature of the muffle furnace reaches 900° C., the muffle furnace is kept warm for 20 minutes and then naturally cooled to room temperature to prepare the expanded graphite.
[0013] (5) The mixture of sodium acetate trihydrate and expanded graphite measured by weight was physically stirred and mixed using a high-speed stirrer at 100 RPM / min for 20 minutes.
[0014] Furthermore, a phase change functional material with a wide temperature range and a preparation method thereof are provided, characterized in that the preparation method comprises the following steps:
[0015] S1: adding the polyethylene glycol into a stainless steel container with an oil bath temperature set at 100° C. for high-temperature physical melting, stirring the polyethylene glycol material at 300 RPM / min for 20 minutes with a high-speed stirrer after the polyethylene glycol material absorbs heat and melts, so that the molten polyethylene glycol is evenly dispersed;
[0016] S2: Weighing the sodium acetate trihydrate and the expanded graphite according to a certain mass, placing them in a glass beaker, and physically stirring and mixing them at 100 RPM / min using a high-speed stirrer for 20 minutes, so that the sodium acetate trihydrate and the expanded graphite can be evenly mixed to obtain a preliminary composite material;
[0017] S3: adding the composite material obtained in S2 into the stainless steel container in S1, and stirring at 300 RPM / min for 45 minutes using a high-speed stirrer to uniformly physically mix the polyethylene glycol, the sodium acetate trihydrate and the expanded graphite;
[0018] S4: After weighing the epoxy resin glue according to a certain mass, add it into the mixed material in step S3, and stir it at 300 RPM / min for 15 minutes using a high-speed stirrer to make the epoxy resin glue uniformly physically mixed with the polyethylene glycol, the sodium acetate trihydrate and the expanded graphite;
[0019] S5: pouring the mixed material prepared in S4 into a plate-shaped mold, die-casting it using a plate press and naturally cooling it to room temperature, and finally obtaining the material having a wide range of phase change temperature and heat absorption and insulation functions.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] A phase change functional material with a wide temperature range and a preparation method thereof, wherein the functional material has two or more typical phase change temperature ranges, wherein a medium-low temperature (<50°C) phase change temperature range realizes temperature control and heat dissipation, and a medium-high temperature (>100°C) phase change temperature range realizes the suppression of thermal runaway or delays thermal runaway.
[0022] A phase-change functional material with a wide temperature range and a preparation method thereof. The functional material has a higher thermal conductivity by adding a thermally conductive filler (expanded graphite). The added epoxy resin glue can enable the functional material to have a certain high-temperature resistance and shaping ability, while suppressing the leakage problem of polyethylene glycol after phase change. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the phase change endothermic test result of pure polyethylene glycol phase change material
[0024] Figure 2 This is the phase change endothermic test result of pure sodium acetate trihydrate inorganic material
[0025] Figure 3 This is a phase change endothermic test result diagram of an implementation case of the present invention
[0026] Specific implementation cases:
[0027] The purpose of the present invention is to provide a phase change functional material with a wide temperature range and a preparation method thereof, so as to solve the single phase change temperature range of traditional phase change materials, broaden the phase change heat absorption range of phase change materials, and construct a thermal management system with full-condition temperature control.
[0028] The invention provides a phase change functional material with a wide temperature range and a preparation method thereof, comprising the following raw materials, measured by weight: 15-30 parts of polyethylene glycol, 20-40 parts of sodium acetate trihydrate, 1-4 parts of expanded graphite, and 5-10 parts of epoxy resin glue.
[0029] The specific embodiments of the present invention will be further explained below with reference to the accompanying drawings and examples.
[0030] The "parts" described in the following examples are all "parts by mass".
[0031] Implementation Case 1
[0032] Step 1: Add the polyethylene glycol into a stainless steel container with an oil bath temperature set at 100° C. for high-temperature physical melting. After the polyethylene glycol material absorbs heat and melts, stir it at 300 RPM / min with a high-speed stirrer for 20 minutes to make the molten polyethylene glycol evenly dispersed.
[0033] Step 2: adding the expanded graphite in a certain amount by mass to the molten polyethylene glycol solution, continuing to stir at 300 RPM / min using a high-speed stirrer for 45 minutes to fully mix the polyethylene glycol solution and the expanded graphite and disperse them evenly, using a plate press to die-cast and naturally cool to room temperature to obtain a polyethylene glycol / expanded graphite composite phase change material.
[0034] Implementation Case 2
[0035] Step 1: Add the sodium acetate trihydrate into a stainless steel container and stir at 100 RPM / min for 20 minutes using a high-speed stirrer to uniformly disperse the sodium acetate trihydrate into fine particles;
[0036] The second step: adding the expanded graphite to the sodium acetate trihydrate according to a certain mass fraction, continuing to stir with a high-speed stirrer at 300RPM / min for 45 minutes, so that the sodium acetate trihydrate and the expanded graphite are fully mixed and evenly dispersed, using a plate press to die-cast and naturally cool to room temperature to obtain a sodium acetate trihydrate / expanded graphite composite phase change material.
[0037] Implementation Case 3
[0038] Step 1: Add the polyethylene glycol into a stainless steel container with an oil bath temperature set at 100° C. for high-temperature physical melting. After the polyethylene glycol material absorbs heat and melts, stir it at 300 RPM / min with a high-speed stirrer for 20 minutes to make the molten polyethylene glycol evenly dispersed.
[0039] Step 2: Weigh the sodium acetate trihydrate and the expanded graphite according to a certain mass and place them in a glass beaker, and use a high-speed stirrer to physically stir and mix them at 100 RPM / min for 20 minutes so that the sodium acetate trihydrate and the expanded graphite can be evenly mixed to obtain a preliminary composite material.
[0040] Step 3: Add the composite material obtained in the second step into the stainless steel container in the first step, and stir at 300 RPM / min for 45 minutes using a high-speed stirrer to uniformly physically mix the polyethylene glycol, the sodium acetate trihydrate and the expanded graphite;
[0041] Step 4: After weighing the epoxy resin glue according to a certain mass, add it into the mixed material in the third step, and stir it at 300RPM / min for 15 minutes using a high-speed stirrer to make the epoxy resin glue uniformly physically mixed with the polyethylene glycol, the sodium acetate trihydrate and the expanded graphite.
[0042] Step 5: pour the mixed material prepared in the fourth step into a plate-shaped mold, use a plate press to die-cast it and naturally cool it to room temperature, and finally obtain the material with a wide range of phase change temperature and heat absorption and insulation functions.
[0043] The melting temperature and melting latent heat of the samples prepared in Cases 1 to 3 were measured using a differential scanning calorimeter (DSC-60plus) in a test temperature range of 30°C to 150°C and a heating rate of 5°C / min.
[0044] Through the specific analysis of the DSC test curve, the composite phase change material presents three typical phase change endothermic peaks in the temperature range. The phase change temperature and phase change endothermic calculation are shown in the following table:
[0045] Implementation Case 1 The first phase transition point Second phase transition point The third phase transition point temperature 51.72℃ -- -- Latent heat 192.80J / g -- -- Implementation Case 2 The first phase transition point Second phase transition point The third phase transition point temperature 61.5℃ 120.5℃ -- Latent heat 163.79J / g 153.76J / g -- Implementation Case 3 The first phase transition point Second phase transition point The third phase transition point temperature 48.67℃ 59.46℃ 131.71℃ Latent heat 33.34J / g 67.11J / g 115.51J / g
Claims
1. A phase change functional material with a wide temperature range and a preparation method thereof, characterized in that: The phase-change functional material with a wide temperature range includes the following raw materials in weight: 15-30 parts of polyethylene glycol, 20-40 parts of sodium acetate trihydrate, 1-4 parts of expanded graphite, and 5-10 parts of epoxy resin glue; the polyethylene glycol weighed by weight is added to a stainless steel container, and the stainless steel container is placed in an oil bath pot with the oil temperature set at 100°C for heating and insulation, then the mixture of the sodium acetate trihydrate and the expanded graphite weighed by weight is added to the polyethylene glycol melted at 100°C in the stainless steel container, and stirred at high speed in a stirrer and fully dispersed, then the epoxy resin weighed by weight is added to the mixture of the polyethylene glycol, sodium acetate trihydrate and expanded graphite in the stainless steel container, and the stirring is continued to make the mixture in the container fully and evenly mixed, and finally cooled to room temperature to prepare the wide temperature range phase-change heat absorption and heat insulation functional material.
2. A phase change functional material with a wide temperature range and a preparation method thereof according to claim 1, characterized in that: The polyethylene glycol is 15-30 parts, preferably one or more of polyethylene glycol 2000, polyethylene glycol 3000, polyethylene glycol 4000, polyethylene glycol 6000, polyethylene glycol 8000, polyethylene glycol 10000 or polyethylene glycol 20000.
3. A phase change functional material with a wide temperature range and a preparation method thereof according to claim 1, characterized in that: The sodium acetate trihydrate is 20-40 parts; (1) Weighing a certain amount of sodium acetate trihydrate and placing it in a glass beaker; (2) adding 1-4 parts of the expanded graphite into a glass beaker, and weighing 1 part, 2 parts, 3 parts or 4 parts by weight; (3) The expanded graphite is prepared by a high-temperature physical thermal expansion method. A certain mass of expandable graphite sheets is weighed and placed in a muffle furnace chamber. The temperature of the muffle furnace is raised to 900° C. for 60 minutes. After the temperature of the muffle furnace reaches 900° C., the temperature is kept at 900° C. for 20 minutes and then naturally cooled to room temperature to prepare the expanded graphite. (4) The mixture of sodium acetate trihydrate and expanded graphite measured by weight was physically stirred and mixed at 100 RPM / min using a high-speed stirrer for 20 minutes.
4. A phase change functional material with a wide temperature range and a preparation method thereof according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1: adding the polyethylene glycol into a stainless steel container with an oil bath temperature set at 100° C. for high-temperature physical melting, stirring the polyethylene glycol material at 300 RPM / min for 20 minutes with a high-speed stirrer after the polyethylene glycol material absorbs heat and melts, so that the molten polyethylene glycol is evenly dispersed; S2: Weighing the sodium acetate trihydrate and the expanded graphite according to a certain mass, placing them in a glass beaker, and physically stirring and mixing them at 100 RPM / min using a high-speed stirrer for 20 minutes, so that the sodium acetate trihydrate and the expanded graphite can be evenly mixed to obtain a preliminary composite material; S3: adding the composite material obtained in S2 into the stainless steel container in S1, and stirring at 300 RPM / min for 45 minutes using a high-speed stirrer to uniformly physically mix the polyethylene glycol, the sodium acetate trihydrate and the expanded graphite; S4: After weighing the epoxy resin glue according to a certain mass, add it into the mixed material in step S3, and stir it at 300 RPM / min for 15 minutes using a high-speed stirrer to make the epoxy resin glue uniformly physically mixed with the polyethylene glycol, the sodium acetate trihydrate and the expanded graphite; S5: pouring the mixed material prepared in S4 into a plate-shaped mold, die-casting it using a plate press and naturally cooling it to room temperature, and finally obtaining the material having a wide range of phase change temperature and heat absorption and insulation functions.